If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -8) = 4x + 2 Reorder the terms: 3(-8 + x) = 4x + 2 (-8 * 3 + x * 3) = 4x + 2 (-24 + 3x) = 4x + 2 Reorder the terms: -24 + 3x = 2 + 4x Solving -24 + 3x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -24 + 3x + -4x = 2 + 4x + -4x Combine like terms: 3x + -4x = -1x -24 + -1x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 -24 + -1x = 2 + 0 -24 + -1x = 2 Add '24' to each side of the equation. -24 + 24 + -1x = 2 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 2 + 24 -1x = 2 + 24 Combine like terms: 2 + 24 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| -12*6-(4+2)= | | 8ax-6x-12a+9=0 | | 16x=1248 | | (-12*6)-4+2= | | 15-2n=n-1 | | 3/4-7/20 | | -7/6=-2n+7/3n | | -12*6-4+2= | | 7/5-3/8k=-2 | | 12(12v+12)-10=2+12v | | 48-6/(3*2)= | | 1/12+x=1/4 | | 48-(6/3)*2= | | (48-6)/3*2= | | 5+-8y=9y+2 | | -3y=-3-x | | 4.5(r-4)=-3(r-1.5) | | .05x+.13(x-3)=.2(x-2) | | 3x-8=6x+1 | | 3h^2+5h/h | | 48-6/3*2=7 | | X^2-2mx+1=0 | | 48-6/3*2= | | 1.2x+6=30 | | 35-5(2x+3)= | | b^2+64=0 | | 36x^2+344x-160=0 | | 2x+11=-13 | | X^2=25/36 | | 2x^2+13a-7=0 | | 10x-3(8-5x)= | | -8c-1=-3 |